Application of coupled electro-thermal and physics-of-failure-based analysis to the design of accelerated life tests for power modules - Musallam, Mahera; Yin, Chunyan; Bailey, Chris; Johnson, C. Mark (Elsevier, 2014)
In the reliability theme a central activity is to investigate, characterize and understand the contributory wear-out and overstress mechanisms to meet through-life reliability targets. For power modules, it is critical to understand the response of typical wear-out mechanisms, for example wire-bond lifting and solder degradation, to in-service environmental and load-induced thermal cycling. This paper presents the use of a reduced-order thermal model coupled with physics-of-failure-based life models to quantify the wear-out rates and life consumption for the dominant failure mechanisms under prospective in-service and qualification test conditions. When applied in the design of accelerated life and qualification tests it can be used to design tests that separate the failure mechanisms (e.g. wire-bond and substrate-solder) and provide predictions of conditions that yield a minimum elapsed test time. The combined approach provides a useful tool for reliability assessment and estimation of remaining useful life which can be used at the design stage or in-service. An example case study shows that it is possible to determine the actual power cycling frequency for which failure occurs in the shortest elapsed time. The results demonstrate that bond-wire degradation is the dominant failure mechanism for all power cycling conditions whereas substrate-solder failure dominates for externally applied (ambient or passive) thermal cycling.